Nitrenoid from Oxime: A Practical Synthesis of Planar Chiral Ferrocenyl Phenanthridines via Nitrene‐Involved Ring‐Expansion Reaction. (30th November 2022) - Li, Na; Hong, Biqiong; Zhao, Jinbo; Gu, Zhenhua
Abstract: Nitrenes and nitrenoids are highly reactive species and the proposed key intermediates in nitrogen‐containing heterocyclic compound synthesis. In this work, we developed a practical method for the synthesis of phenanthridines by the reaction of oximes and Grignard reagents (with or without diethylzinc) via ring‐expansion of magnesium coordinated nitrenoid complex as the key step. The method has been used to synthesize optically active planar chiral ferrocenyl phenanthridines. Abstract : A new Grignard reagent‐mediated synthesis of ferrocene‐based phenanthridines from oximes was developed. The tertiary magnesium‐zinc nitrenoid was proposed as the key intermediate, which underwent ring‐expansion/rearrangement to form the pyridine skeleton.